Hierarchical vertical graphene nanotube arrays via universal carbon plasma processing strategy : a platform for high-rate performance battery electrodes - Ouyang, Bo (2019)
Tailoring graphene-based nanostructures with numerous edges and large porosity is critical in developing high-capacity and fast rate-response Na-ion battery. Here, we report a rapid and generalized strategy for preparation of hierarchical vertical graphene nanotube (hVGT) array via carbon plasma processing of CuO nanowires. A plausible mechanism is provided with the successful extension of such approach to grow hVGT array on different nanostructure templates such as Ni3S2, NiO and Co3O4. Benefiting from such unique structural advantages including high electrical conductivity, strong mechanical stability and highly porous structure, the self-supported MoS2 nano-crystals anchored hVGT (MVGT) nano-frameworks deliver satisfactory Na-ion storage properties with enhanced rate capability and long-term cycling stability. Hence, it is worth emphasizing that this deterministic and plasma-based dry-synthesis method to fabricate hVGT architecture could provide new avenues in designing and fabricating high-performance carbon-based electrodes for energy storage devices.